Perceptions, Motivations and Practices for Indigenous Engagement in Marine Science in Australia - Hedge, Paul; van Putten, Elizabeth Ingrid; Hunter, Cass; Fischer, Mibu (Frontiers in Marine Science, 2020)
Australian science has evolved to include a number of initiatives designed to promote and guide ethical and culturally appropriate Indigenous participation and engagement. While interest and overall engagement between Indigenous people and marine scientists appears to have grown in the last decade there are also signs that some researchers may not be setting out to engage with Indigenous Australians on the right foot. This research seeks to move beyond anecdotal evidence about engagement of marine researchers with Indigenous Australians by gathering empirical information from the scientists’ perspective. Our survey of 128 respondents showed that 63% (n=79) of respondents have engaged with Indigenous communities in some way throughout their career, however, most marine research projects have not included Indigenous engagement and when it occurs it is often shorter than three years in duration. Responses indicated that the majority of marine scientists see mutual benefits from engagement, do not avoid it and believe it will become more important in the future. We identify a number of challenges and opportunities for marine research institutions, marine researchers and Indigenous communities if positive aspirations for engagement are to be converted to respectful, long-term and mutually beneficial engagement.